The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-879x2002000800005
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in young women of the city of São Paulo, Brazil: correlation with both collagen type I alpha 1 gene polymorphism and clinical aspects

Abstract: Osteoporosis is a multifactorial disease with great impact on morbidity and mortality mainly in postmenopausal women. Although it is recognized that factors related to life-style and habits may influence bone mass formation leading to greater or lower bone mass, more than 85% of the variation in bone mineral density (BMD) is genetically determined. The collagen type I alpha 1 (COLIA1) gene is a possible risk factor for osteoporosis. We studied a population of 220 young women from the city of São Paulo, Brazil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
3
1
3
Order By: Relevance
“…A similar finding was reported by Guzeloglu-Kayisli et al [13], Barros et al [17] and Berg et al [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A similar finding was reported by Guzeloglu-Kayisli et al [13], Barros et al [17] and Berg et al [28].…”
Section: Discussionsupporting
confidence: 89%
“…We studied a G!T polymorphism at the first base of a binding site for the transcription factor Sp1 in the first intron of the COLIAI gene by polymerase chain reaction (PCR)-based method described by Barros et al, [17] resulting in 264 bp fragment of regulatory region of COLIAI gene.…”
Section: Dna Analysismentioning
confidence: 99%
“…8 Earlier studies reported lower hip fracture rates in Latin America than in U.S. or European whites. [9][10][11][12] However, the number of women at risk of osteoporosis and hip fracture is increasing in Latin America. The number of hip fractures for women and men aged 50-64 in Latin America will increase by 400%, while in ages 65 and over the increase will be a staggering 700% in 2050 as compared to the prevalence in 1950.…”
mentioning
confidence: 99%
“…This fact is directly related to the increased production of sex hormones, particularly the already mentioned action of estrogen on osteoclast activity 21 . In addition, considering lumbar spine and femoral neck BMD values of 1.200 (g/cm²) and 0.965 (g/cm²) 23 during peak bone mass, postpubertal adolescent girls already reached approximately 90% and 109% of the expected values, respectively. Longitudinal studies also reported that 90% to 100% of peak bone mass is acquired at the end of adolescence 5,6 .…”
Section: Discussionmentioning
confidence: 97%